Learn in your speed, with individual attention - Teachoo Maths 1-on-1 Class

Examples

Example 1

Example 2

Example 3

Example 4

Example 5 Important

Example 6

Example 7 Important

Example 8

Example 9

Example 10

Example 11 Important

Example 12

Example 13 Important

Example 14

Example 15 Important

Example 16 You are here

Example 17 Important

Example 18

Example 19 Important

Question 1 Deleted for CBSE Board 2024 Exams

Question 2 Deleted for CBSE Board 2024 Exams

Question 3 Deleted for CBSE Board 2024 Exams

Question 4 Important Deleted for CBSE Board 2024 Exams

Question 5 Important Deleted for CBSE Board 2024 Exams

Question 6 Deleted for CBSE Board 2024 Exams

Question 7 Deleted for CBSE Board 2024 Exams

Question 8 Deleted for CBSE Board 2024 Exams

Question 9 Important Deleted for CBSE Board 2024 Exams

Question 10 Important Deleted for CBSE Board 2024 Exams

Question 11 Important Deleted for CBSE Board 2024 Exams

Question 12 Deleted for CBSE Board 2024 Exams

Question 13 Important Deleted for CBSE Board 2024 Exams

Question 14 Important Deleted for CBSE Board 2024 Exams

Question 15 Important Deleted for CBSE Board 2024 Exams

Chapter 4 Class 12 Determinants

Serial order wise

Last updated at June 11, 2023 by Teachoo

Example 16 Solve the system of equations 2x + 5y = 1 3x + 2y = 7 Step 1 Write equation as AX = B [■8(2&5@3&2)] [■8(𝑥@𝑦)] = [■8(1@7)] A = [■8(2&5@3&2)] , X = [■8(𝑥@𝑦)] , B = [■8(1@7)] Step 2 Calculate |A|, A = [■8(2&5@3&2)] |A| = |■8(2&5@3&2)| = 2 × 2 – 5 × 3 = 4 – 15 = – 11 Since |𝑨| ≠ 0, System is consistent and the system of equations has a unique solution AX = B X = A-1 B Step 3 Calculating X = A-1 B Here, A-1 = 1/(|A|) adj (A) adj A = [■8(2&5@3&2)] = [■8(2&−5@−3&2)] Now, A-1 = 1/(|A|) adj A Putting values = 𝟏/(−𝟏𝟏) [■8(𝟐&−𝟓@−𝟑&𝟐)] & B = [■8(1@7)] Now X = A-1 B [■8(𝑥@𝑦)] = (−1)/11 [■8(2&−5@−3&2)] [■8(1@7)] [■8(𝑥@𝑦)] = (−1)/11 [■8(2(1)+(⤶7−5)7@−3(1)+2(7))] [■8(𝑥@𝑦)] = (−1)/11 [■8(2−35@−3+14)] = (−1)/11 [■8(−33@11)] = [■8(−33 × (−1)/11@11 × (−1)/11)] [■8(𝑥@𝑦)] = [■8(3@−1)] Hence x = 3 & y = – 1